Analysis of the Influence of Cracked Sleepers under Static Loading on Ballasted Railway Tracks - Laura Montalbán Domingo; Clara Zamorano Martín; Cristina Palenzuela Avilés; Julia I. Real Herráiz (The Scientific World Journal)
The principal causes of cracking in prestressed concrete sleepers are the dynamic loads induced by track irregularities and imperfections in the wheel-rail contact and the in-phase and out-of-phase track resonances. The most affected points are the mid-span and rail-seat sections of the sleepers. Central and rail-seat crack detection require visual inspections, as legislation establishes, and involve sleepers’ renewal even though European Normative considers that thicknesses up to 0.5 mm do not imply an inadequate behaviour of the sleepers. For a better understanding of the phenomenon, the finite element method constitutes a useful tool to assess the effects of cracking from the point of view of structural behaviour in railway track structures. This paper intends to study how the cracks at central or rail-seat section in prestressed concrete sleepers influence the track behaviour under static loading. The track model considers three different sleeper models: uncracked, cracked at central section, and cracked at rail-seat section. These models were calibrated and validated using the frequencies of vibration of the first three bending modes obtained from an experimental modal analysis. The results show the insignificant influence of the central cracks and the notable effects of the rail-seat cracks regarding deflections and stresses.